Effective action for QED4 through ζ function regularization - Beneventano, Carlota Gabriela (2001)
We obtain, through ζ function methods, the one-loop effective action for massive Dirac fields in the presence of a uniform, but otherwise general, electromagnetic background. After discussing renormalization, we compare our ζ function result with Schwinger's proper-time approach.